2018
DOI: 10.1002/celc.201801181
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tungsten Trioxide/Hematite Core‐Shell Nanoarrays for Efficient Photoelectrochemical Water Splitting

Abstract: Hematite, with a band gap of 2.0∼2.2 eV suitable for visible light absorption, has emerged to be a promising photoanode material for photoelectrochemical (PEC) catalysis of the oxygen evolution reaction (OER). Herein, we proposed the design and fabrication of a WO3/α‐Fe2O3 core‐shell heterojunction structure, aiming at alleviating the severe mismatch between the relatively long light penetration depth and the extremely short holes diffusion length in α‐Fe2O3. The WO3 nanoarray underlayer is grown directly on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…( 8) as the A HE one and the Bprocess in the same equation as the hematite-catalyzed ORR, one can assume that the parameters S o , g A , h A are essentially identical for all ceramic samples, whereas the p, g B , h B parameters will be sample-characteristic. Then, equation (10) can be rewritten as equation ( 11): (11) where B J and C J represent site-characteristic parameters easily determined from the linear fit of experimental data such as in Figure 11. The corresponding values of the coefficients B J and C J are listed in Table 1.…”
Section: Archaeometric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 8) as the A HE one and the Bprocess in the same equation as the hematite-catalyzed ORR, one can assume that the parameters S o , g A , h A are essentially identical for all ceramic samples, whereas the p, g B , h B parameters will be sample-characteristic. Then, equation (10) can be rewritten as equation ( 11): (11) where B J and C J represent site-characteristic parameters easily determined from the linear fit of experimental data such as in Figure 11. The corresponding values of the coefficients B J and C J are listed in Table 1.…”
Section: Archaeometric Implicationsmentioning
confidence: 99%
“…[1] Among other compounds, hematite (α-Fe 2 O 3 ) has claimed attention as a photoanode for producing the oxygen evolution reaction (OER) because of its low cost, stability in contact with alkaline solutions, n-type semiconducting properties and band gap of around 2.0 eV. Processes catalyzed by hematite include oxygen reduction reaction (ORR), [2][3][4][5] photoelectrochemical water splitting, [6][7][8][9][10][11] and hydrogen peroxide oxidation. [12] The electrochemistry of hematite has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…also reported that colloidal WO 3 nanowires for solar water splitting and it is reached 1.96 mA cm −2 at 1.23 V RHE under AM1.5G solar irradiation [47] . WO 3 based materials displayed enhanced photo/catalytic activities due to the increasing charge separation, stability and alleviate photogenerated holes accumulation on the surface [48–52] . Nonetheless, we believe that the overall catalytic activity of WO 3 NLs‐ITO in this study is somewhat limited due to the low content of catalyst on the electrode.…”
Section: Resultsmentioning
confidence: 68%
“…[47] WO 3 based materials displayed enhanced photo/catalytic activities due to the increasing charge separation, stability and alleviate photogenerated holes accumulation on the surface. [48][49][50][51][52] Nonetheless, we believe that the overall catalytic activity of WO 3 NLs-ITO in this study is somewhat limited due to the low content of catalyst on the electrode. Our future studies will attempt to improve on these results through further fine-tuning of the BCP inclusion process for synthesising thicker and denser (in height and diameter) metal oxide structures.…”
Section: Chemelectrochemmentioning
confidence: 82%
“…The cathodic shift in the onset potential is more pronounced in the 0.5W:α-Fe 2 O 3 /MoS 2 electrode, which implies a shift of the conduction band in the negative region and facile charge transfer pathways. 50,51 The photocurrent response and stability vs time (i−t) curves of pure α-Fe 2 O 3 , 0.25W:α-Fe 2 O 3 , 0.5W:α-Fe 2 O 3 , 1W:α-Fe 2 O 3 , and 0.5W:α-Fe 2 O 3 /MoS 2 were evaluated by chronoamperometry at a constant applied potential of 1.23 V vs RHE for four on−off cycles under 1-sun illumination, and the results are shown in Figure S7c,d. The photocurrents in these four cycles were measured under periodic illumination (30 s light on and 15 s light off) in 1 M NaOH solution as an electrolyte.…”
mentioning
confidence: 99%